2017
DOI: 10.1016/j.reprotox.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal BPA exposure alters body weight and composition in a dose specific and sex specific manner: The addition of peripubertal exposure exacerbates adverse effects in female mice

Abstract: Body weight (BW) and body composition were examined in CD-1 mice exposed perinatally or perinatally and peripubertally to 0, 0.25, 2.5, 25, or 250 μg BPA/kg BW/day. Our goal was to identify the BPA dose (s) and the exposure window(s) that increased BW and adiposity, and to assess potential sex differences in this response. Both perinatal exposure alone and perinatal plus peripubertal exposure to environmentally relevant levels of BPA resulted in lasting effects on body weight and body composition. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 69 publications
6
83
0
1
Order By: Relevance
“…Further research using fetal liver tissue has also identified specific relationships between BPA and repetitive DNA elements, where nonmonotonic relationships between BPA exposure and DNA methylation were observed in several repeat families, including LINE1 [78]. Nonmonotonic relationships have previously been observed in prenatal mouse exposure models both with respect to both epigenomic and metabolic end points [79][80][81]. However, previous research, using both LUMA and pyrosequencing, did not identify a relationship between global methylation and BPA exposure in fetal liver or kidney, but did note a positive relationship between BPA exposure and LINE1 methylation in the placenta [82].…”
Section: Endocrine Disruptorsmentioning
confidence: 84%
“…Further research using fetal liver tissue has also identified specific relationships between BPA and repetitive DNA elements, where nonmonotonic relationships between BPA exposure and DNA methylation were observed in several repeat families, including LINE1 [78]. Nonmonotonic relationships have previously been observed in prenatal mouse exposure models both with respect to both epigenomic and metabolic end points [79][80][81]. However, previous research, using both LUMA and pyrosequencing, did not identify a relationship between global methylation and BPA exposure in fetal liver or kidney, but did note a positive relationship between BPA exposure and LINE1 methylation in the placenta [82].…”
Section: Endocrine Disruptorsmentioning
confidence: 84%
“…Further, while in utero THC exposure appears to alter social behavior in a sexually divergent manner 26 , here we have observed no differences between male and female progeny perinatally exposed to THC. The timing-specificity of longterm effects of drug exposure with regards to sexually dimorphic outcomes has been noted with several other substances, including tobacco 44 , the anesthetic drug isoflurane 45 and toxins such as lead 46 and bisphenol-A 47 .…”
Section: Discussionmentioning
confidence: 98%
“…For dams exposed to 250 μg BPA, mean total BPA levels measured were 1.48 +/− 2.33 ng/ml and 4.0 ng/ml in the pooled blood from their fetuses. Again, measurements of unconjugated BPA were below the detectability of the assay [12]. Dams were allowed to deliver naturally, and the litters were culled to 8 pups per mother one day after birth.…”
Section: Methodsmentioning
confidence: 99%
“…BPA is able to cross the human placenta and has been detected in its unconjugated form at relatively high levels in the human maternal-fetal placental unit [10,11]. In our model of maternal exposure to BPA during gestation or gestation and lactation, unconjugated BPA was below the detectability of the assay (< 0.3 ng/ml) in animals exposed to up to 250 μg BPA/kg BW/day [12]; hence, the BPA internal dose in animals in the current study should be well within the range reported in humans.…”
Section: Introductionmentioning
confidence: 99%